Analysis of efficiency factors of companies in Serbia based on artificial neural networks - Radojko Lukic (Anali Ekonomskog fakulteta u Subotici, 2022)
This paper investigates the influence of certain factors on the efficiency of companies in Serbia using artificial neural networks. According to the results of empirical research using artificial neural networks, the significance of some observed factors on the efficiency of companies in Serbia is as follows: net profit 55.5%, operating revenues 59.4%, operating assets 52.8%, capital 59.6 %, loss 100% and number of employees 51.3%. In order to improve the efficiency of companies in Serbia in the future, it is necessary, in the first place, to manage profits as efficiently as possible (i.e. to reduce losses as much as possible). This is also achieved with the most efficient management of sales, assets, capital and human resources (training, rewarding, job advancement, and flexible employment). Accelerated digitalization of the entire business certainly plays a significant role in that.